Implementation Findings from an Effectiveness-Implementation Trial of Tablet-Based Parent Training in Pediatric Primary Care - Breitenstein, Susan M. (Fam Syst Health, 2019)
INTRODUCTION: The use of mobile delivery to deliver parent training can address barriers to access and improve the translation of interventions in existing settings like pediatric primary care. Studying implementation provides critical information to identify and address barriers and facilitators and inform sustainability efforts. METHODS: This study was a descriptive evaluation using the RE-AIM framework as part of a Hybrid Type I Effectiveness-Implementation trial of the ezParent Program within four pediatric primary care clinics. We collected data before, during, and after implementation to evaluate provider implementation and their perspectives on program benefits and barriers to implementation. RESULTS: On average 14% of eligible parents were introduced to the study. Of these parents, 78% expressed interest in participating and 37% enrolled in the study. Seventy-eight percent of staff providers (n =36) implemented the procedures at least once and among those who implemented three or more times (n = 24), 79% maintained implementation for six months. Barriers to implementation include limited time, lack of information, and full practice buy-in and engagement. DISCUSSION: Implementation fidelity may improve with additional education and training of the interdisciplinary team, clear messaging regarding the purpose and content of the ezParent program, defining roles within the care team, identifying practice champions, and use of the EHR. Findings from this evaluation, data from the RCT and literature to support intervention effectiveness and implementation, will be used to develop an implementation toolkit to include specific strategies for implementation and ideas for local adaptations.